A composite catalyst material based on rapid degradation of microplastics and its preparation method and application
Through the preparation of composite catalyst materials, the rapid degradation of microplastics by hydrolysis and solvothermal reaction technology is used to solve the problem of low resource utilization rate of microplastic degradation in the existing technology, and the efficient and convenient degradation and resource utilization of microplastics are achieved. Green and environmentally friendly solutions.
Patent Information
- Application Number
- CN202310291334.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-03-21
AI Technical Summary
In the prior art, the resource utilization rate of microplastic degradation is low, and the traditional removal methods are inefficient, which cannot effectively solve the problem of microplastic pollution.
The composite catalyst material is used to carry out hydrolysis reaction through alkaline aqueous solution and accelerator, and then undergo a solvothermal reaction with ferric chloride to prepare a catalyst material that can quickly degrade microplastics, and the material is catalyzed to remove organic pollutants in the wastewater.
It improves the degradation and recycling rate of microplastics, achieves efficient and convenient degradation and resource utilization of microplastics, reduces its toxic side effects, and provides a green and environmentally friendly solution.
Smart Images

Figure CN116422372B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water environment treatment, and in particular to a composite catalyst material based on rapid degradation of microplastics, and a preparation method and application thereof. Background Art
[0002] Plastics are the world's largest synthetic consumer product, with annual production reaching 359 million tons in 2018. Plastics are the material of choice in many fields because of their light weight, low cost, easy processing and diverse properties. Despite these considerable advantages, the resulting plastic pollution has an impact on the environment and human health. Only a very small amount of plastic is recycled each year, and most discarded plastics are landfilled or incinerated. Incineration partially recovers the energy stored in plastic waste in the short term, but does not create economic value or reduce material resource consumption in the long term, while releasing carbon dioxide and other harmful gases. These plastics that are not degraded by landfill or incineration are exposed to the natural environment, and the fragmentation of plastic fragments caused by erosion will produce smaller plastic particles, namely microplastics and nanoplastics. Microplastics (MPs) are any plastic fragments with a size less than 5 mm, with no specific lower limit. It is reported that an estimated 1.5 million tons of MPs are released into aquatic environments each year. Due to their small size, microplastics can be ingested by small organisms with lower nutrient levels and accumulate in the food chain of the ecosystem. Microplastics have been detected in a variety of aquatic species and even in the human placenta; in a new study, scientists have found microplastic particles in human blood for the first time. Due to their large number and small size, MPs can easily enter the human body through the food chain. Therefore, compared with large plastics, MPs are much more harmful to humans. A large number of studies have shown that MPs can seriously damage the growth and reproduction of organisms and even cause death. Therefore, how to remove microplastics in the aquatic environment has received more and more widespread attention.
[0003] At present, typical microplastic separation technologies include: membrane filtration, coagulation-flocculation, biological and chemical digestion, electrostatic separation, etc. Among them, factors such as the shape, size and mass of microplastic particles have a great influence on the removal effect of membrane filtration, blocking the ultrafiltration membrane pores, seriously aggravating membrane pollution and deteriorating the removal performance; coagulation-flocculation, as a traditional water treatment process, is easy to operate and low-cost. It can effectively remove suspended colloidal particles in water and has also been proven to be used for the removal of microplastics, but there are few literatures on the characterization of precipitated flocculants; biological and chemical digestion technologies are highly efficient in removing microplastics, but the treatment process has harsh treatment conditions and high costs. In addition, microplastic degradation technologies include: biodegradation, advanced oxidation processes, Fenton reactions, electrochemistry, photocatalytic degradation, etc. However, separation and degradation of microplastics cannot completely remove them. Due to the inefficiency of these methods and the urgency of microplastic pollution, the research community is mainly focused on achieving effective chemical reuse. / Upgrading recycling technology is also known as resource technology. Through reasonable design to achieve sustainable energy supply and low carbon emissions, chemical recycling will be the most direct and effective way to achieve plastic recycling. The common chemical recycling method for plastics and microplastics is to depolymerize them into oligomers or monomers, separate and purify them as raw materials for further production and conversion into high-quality products in the textile and other industries. The present invention aims to rapidly degrade microplastics while enhancing their resource utilization rate and reducing their toxic side effects, thereby providing a new method for the degradation, removal and resource utilization of microplastics. Summary of the invention
[0004] The purpose of the present invention is to provide a composite catalyst material based on the rapid degradation of microplastics and its preparation method and application, so as to solve the technical problem of low resource utilization rate of microplastic degradation in the prior art.
[0005] The present invention provides a composite catalyst material and a preparation method and application thereof, comprising the following steps:
[0006] (1) adding an alkaline aqueous solution to the microplastics and then adding an accelerator to perform a hydrolysis reaction to obtain a first reaction solution;
[0007] (2) adding an acid to the first reaction solution to adjust the pH to acidic, and then adding ferric chloride to carry out a solvothermal reaction to obtain a second reaction solution;
[0008] (3) Post-treating the second reaction liquid to obtain a composite catalyst material.
[0009] Furthermore, in the hydrolysis reaction of step (1), the dosage of the microplastic is 0.5 to 50 g / L, the microplastic is one of polyethylene terephthalate, polypropylene terephthalate and polybutylene terephthalate, and the particle size of the microplastic is 100 nm to 1000 μm.
[0010] Optionally, the particle size of the microplastic is further preferably 25 um to 250 um, and further preferably 50 to 100 um. The microplastic is further preferably 2 to 20 g / L, and further preferably 5 to 10 g / L.
[0011] Furthermore, in the hydrolysis reaction of step (1), the alkaline aqueous solution is a NaOH aqueous solution, and the NaOH concentration is 10 to 100 g / L; the temperature of the hydrolysis reaction is 60 to 140° C., and the time of the hydrolysis reaction is 30 to 150 min.
[0012] The main components of the first reaction solution obtained in step (1) are sodium terephthalate and ethylene glycol, and it contains a small amount of polymers: quinone phthalocyanine (AQDC), ethylene glycol dicarboxylate (DEG), trimellitic acid (TMA), etc., and also contains trace small molecules: 1,4-benzenedicarboxaldehyde, acetylaminobenzoic acid, acetic acid, dimethyl ether, etc.
[0013] Optionally, the NaOH concentration is further preferably 40 to 80 g / L, and further preferably 60 to 70 g / L. The temperature of the hydrolysis reaction is further preferably 80 to 130° C., and further preferably 100 to 120° C. The time of the hydrolysis reaction is further preferably 40 to 100 min, and further preferably 60 to 80 min.
[0014] Furthermore, in step (1), the accelerator is a quaternary ammonium salt type cationic surfactant.
[0015] Furthermore, in step (1), the accelerator is one or more of dodecyltrimethylammonium bromide (chloride), dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide (chloride), hexadecyldimethylbenzylammonium chloride, and octadecyldimethylhydroxyethylammonium nitrate.
[0016] Furthermore, in step (2), the molar ratio of the first reaction solution to ferric chloride is 1:(0.5-3); the temperature of the solvent thermal reaction is 100-300° C., and the time of the solvent thermal reaction is 2-48 hours.
[0017] Optionally, the molar ratio of the first reaction liquid to ferric chloride is more preferably 1: (1-2), and more preferably 1: 1. The reaction temperature of the solvothermal reaction is more preferably 120-250°C, and more preferably 150°C.
[0018] Furthermore, the post-treatment includes: centrifuging the second reaction liquid to separate the solid and liquid, washing with DMF and ethanol continuously, and placing the obtained solid in a vacuum drying oven; wherein the vacuum drying temperature is 50 to 150° C., and the vacuum drying time is 2 to 48 hours.
[0019] Optionally, the vacuum drying temperature is more preferably 80 to 120° C., and more preferably 100° C. The vacuum drying time is more preferably 12 to 36 hours, and more preferably 24 hours.
[0020] The invention also provides a composite catalyst material prepared by the method.
[0021] The invention also provides application of the composite catalyst material in degrading organic pollutants in waste water.
[0022] The present invention provides a composite catalyst material, a preparation method and an application thereof, which utilize the principle of polyester alkaline hydrolysis to rapidly degrade microplastics. By adding an accelerator, the prepared composite catalyst material is closer to a pure MOF catalyst, thereby improving the degradation and recycling rate of microplastics. The composite catalyst can catalyze the degradation and removal of organic pollutants in wastewater, thereby solving the technical problem of low resource utilization rate of microplastic degradation in the prior art, and is green, environmentally friendly, efficient and convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a SEM image of the composite catalyst prepared by not adding an accelerator and not fully filtering and fully filtering provided in Example 1;
[0025] Among them, A is the SEM image of the catalyst prepared without sufficient filtration; B is the SEM image of the catalyst prepared by sufficient filtration.
[0026] Figure 2 This is the curve of the change of the residual rate of RhB degradation by single ozone / catalytic ozone oxidation over time provided in this Example 1.
[0027] Figure 3 The SEM images of the composite catalyst prepared by adding different accelerators provided in Comparative Example 1;
[0028] Among them, A is a SEM image of the composite catalyst prepared by adding dodecyltrimethylammonium bromide (DTAB) accelerator; B is a SEM image of the composite catalyst prepared by adding hexadecyltrimethylammonium bromide (CTAB) accelerator.
[0029] Figure 4 This is a SEM image of the composite catalyst prepared by replacing the first reaction solution with pure terephthalate solution provided in Comparative Example 2.
[0030] Figure 5 This is a comparison chart of the degradation rates with and without the addition of an accelerator under the conditions of a certain degradation time and temperature and different concentrations of NaOH provided in Example 2.
[0031] Figure 6 This is a comparison chart of the degradation rates with and without the addition of an accelerator under the conditions of a certain degradation concentration, time and different degradation temperatures provided in Example 3.
[0032] Figure 7 This is a comparison chart of the degradation rates with and without the addition of an accelerator under the conditions of a certain degradation concentration and temperature and different degradation times provided in Example 4. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The present embodiment provides a method for rapidly degrading microplastics and using the degradation waste liquid thereof to prepare a composite catalyst material, the specific steps comprising: (1) adding an alkaline aqueous solution to the microplastics, and then adding an accelerator (for a hydrolysis reaction) to obtain a first reaction liquid; (2) adding an acid to the first reaction liquid to adjust the pH to acidic, and then adding ferric chloride for a solvothermal reaction to obtain a second reaction liquid; (3) post-treating the second reaction liquid to obtain a composite catalyst material.
[0036] The microplastics in this embodiment are selected from PET as an example. The rapid degradation experiment of microplastics is step (1), which specifically includes: selecting 0.5g / L of PET microplastics and 60g / L of NaOH without adding an accelerator. Mix the alkali solution and PET microplastics and put them into a dyeing machine, heat them to 100°C at 3°C / min, keep them warm for 60 minutes and then cool them down to obtain the first reaction liquid. After the treatment, take out the first reaction liquid, filter-wash-dry-weigh (filter out the PET microplastics that have not been completely depolymerized, retain the filtrate, wash with ethanol 3 times and deionized water 3 times), and calculate the degradation rate.
[0037] The experiment of recycling the waste liquid after the degradation of the above-mentioned microplastics to prepare a composite catalyst material includes steps (2) and (3).
[0038] The step (2) specifically comprises: using the above degradation rate to estimate the concentration of the mixture in the first reaction liquid after degradation. Acid is added to the first reaction liquid to adjust the pH to 3-4, and ferric chloride is added in an amount equal to the mole of the first reaction liquid, and stirred at a constant temperature of 20-25° C. to fully dissolve. After the reaction is completed, a second reaction liquid is obtained.
[0039] Step (3) specifically includes: transferring the second reaction liquid to a stainless steel reactor containing a polytetrafluoroethylene liner for a solvothermal reaction, and reacting at 150°C for 18 hours. The second reaction liquid is subjected to centrifugal solid-liquid separation, and is washed with DMF and ethanol for 2 to 3 times to remove residual raw materials and DMF. Finally, the solid obtained by centrifugation is placed at 100°C and vacuum dried for 24 hours to obtain the composite catalyst material obtained by resource recovery. The obtained composite catalyst material mainly has a needle-like morphology. The surface of the catalyst prepared without sufficient filtration has flocculent oligomers remaining, while the surface of the catalyst prepared by sufficient filtration has a large number of particles coated, which is suspected to be oxidized to form iron oxide, such as Figure 1 shown.
[0040] The obtained composite catalyst material can be used to catalyze the degradation of organic pollutants in wastewater by ozone. The experimental process for testing its degradation performance is as follows: prepare 300mL 40mg·L -1 Rhodamine B (RhB) solution was placed in a wide-mouth glass reactor, and then 100 mg of the composite catalyst made from the wastewater resource recovery after the degradation of PET microplastics was added. After adsorption and desorption equilibrium for 30 minutes, 5 mL of the sample was taken and ozone gas was introduced at a flow rate of 60 mL min -1 , and the catalytic ozone oxidation degradation of RhB reaction began. During the degradation process, 5 mL of sample was taken every 1 min, filtered through a 0.45 μm aqueous filter head, and then allowed to stand for the measurement of RhB concentration. The ozone molecules and other ROS in the residual sample were oxidized with 0.1 mol·L -1 Na 2 S 2 O 3 The solution was quenched to eliminate the continuous effects of residual ozone and ROS that affect the experimental results. As a control, ozone alone was also carried out under the same experimental conditions, but no catalyst was added to the degradation system. The ratio of the sample concentration Ct taken at the time points of 0min, 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, and 10min to the initial concentration of RhB C0 was used as the vertical coordinate, and the time point was used as the horizontal coordinate to draw a curve of the change of the residual rate of RhB degradation by ozone alone / catalytic ozone oxidation over time. The catalytic activity of the catalytic ozone oxidation system was evaluated using the degradation rate as an indicator and the single ozone oxidation performance as a control. The results are shown in Figure 2 shown.
[0041] The absorbance of the sample (RhB solution) was measured at λ = 554 nm (the maximum absorption wavelength of the RhB solution) using an ultraviolet-visible spectrophotometer, and the concentration of the sample RhB was calculated using the Lambert-Beer law. 0 -C t ) can be calculated by the following formula:
[0042]
[0043] Where C t is the concentration of RhB solution at time t; C 0 is the initial concentration of RhB solution; A t is the absorbance of RhB solution at time t, A 0 is the initial absorbance of RhB; (C 0 -C t ) / C 0 is the degradation rate of RhB at time t.
[0044] Depend on Figure 2 It can be seen that in the RhB-catalyzed ozone oxidation stage, the degradation rate in the first 1-2 min is limited by the solubility of gaseous ozone molecules, that is, the oxidation degradation of RhB is closely related to the solubility of gaseous ozone molecules. 3 It is related to the mass transfer (dissolution) ability of the molecule in water. After this stage, the concentration of RhB changes significantly with time. The degradation of RhB in the ozone system alone takes about 8 minutes to complete; the pure MIL-53 (Fe) MOF catalyst can achieve complete degradation in 3-4 minutes; the composite catalyst material prepared by the resource utilization of wastewater after degradation of PET microplastics also takes about 4 minutes to achieve complete degradation.
[0045] Comparative Example 1
[0046] As an experimental control for the rapid degradation of microplastics and the use of the degradation waste liquid for preparing the composite catalyst material in Example 1, different accelerators were added in step (1) to obtain multiple first reaction liquids. Under the same experimental conditions, the morphologies of the composite catalyst materials obtained were similar to rectangular and diamond blocks, and there were needle-like objects formed by the accelerator on the catalyst surface, such as Figure 3 shown.
[0047] Comparative Example 2
[0048] As an experimental control for the rapid degradation of microplastics and the use of the degradation waste liquid for preparing the composite catalyst material in Example 1, the first reaction liquid in step (1) was replaced with terephthalate. Under the same experimental conditions, the morphology of the composite catalyst material obtained is as follows: Figure 4 shown.
[0049] By comparison, it was concluded that the addition of an accelerator made the prepared composite catalyst closer to a pure MOF catalyst, thereby improving the resource utilization rate of microplastic degradation. By comparing the effects of different accelerators, the accelerator dodecyltrimethylammonium bromide (DTAB) had the fastest degradation rate for PET and the highest resource utilization rate; this may be because of its short molecular chain and the bromine atoms in the structure that promoted the decomposition of PET.
[0050] Example 2
[0051] A method for rapid degradation of microplastics comprises the following steps: selecting and fixing PET microplastics at 5 g / L, adjusting the NaOH concentration to 10 g / L, 20 g / L, 40 g / L, 60 g / L, 80 g / L, and 100 g / L, and not adding an accelerator. As three groups of controls, under the same experimental conditions, 1.5 g / L dodecyltrimethylammonium bromide (DTAB), 1.5 g / L hexadecyltrimethylammonium bromide (CTAB), and an accelerator mixed in a ratio of 1:1 are added respectively. The solution and PET microplastics are mixed and put into a dyeing machine, heated to 100°C, kept warm for 60 minutes, and then cooled to obtain a first reaction solution.
[0052] After the treatment, the first reaction liquid was taken out, PET was filtered out, washed with ethanol 3 times, washed with deionized water 3 times, dried, weighed, and the degradation rate was calculated. Figure 5 As shown. Figure 5 It can be seen that as the NaOH concentration increases, the degradation rate increases accordingly; when the NaOH concentration is 60g / L and above, the degradation rate after adding the accelerator reaches more than 95%.
[0053] Example 3
[0054] A method for rapid degradation of microplastics includes the following steps: selecting a fixed PET microplastic of 5 g / L, taking a NaOH mass concentration of 60 g / L as an example, and not adding an accelerator. Mixing the solution and the PET microplastics into a dyeing machine, changing the temperature to 30°C, 60°C, 90°C, 100°C, and 120°C, keeping the temperature for 60 minutes, and then cooling to obtain a first reaction solution. As a control, under the same experimental conditions, 1.5 g / L dodecyltrimethylammonium bromide (DTAB), hexadecyltrimethylammonium bromide (CTAB) and an accelerator mixed in a ratio of 1:1 are added.
[0055] After the treatment, the first reaction liquid was taken out, PET was filtered out, washed with ethanol 3 times, washed with deionized water 3 times, dried, weighed, and the degradation rate was calculated. Figure 6 As shown. Figure 6 It can be seen that as the temperature increases, the degradation rate also increases. After adding the accelerator at 100°C, the degradation rate can reach more than 90%. Figure 6 It can be seen that as the temperature increases, the degradation rate increases. At 100°C, the degradation rate reaches more than 90% after adding the accelerator.
[0056] Example 4
[0057] A method for rapid degradation of microplastics comprises the following steps: selecting and fixing PET microplastics at 5 g / L, NaOH mass concentration at 60 g / L, and no accelerator. Mixing the solution and PET microplastics into a dyeing machine, heating to 100°C and changing the time by 30 min, 60 min, 90 min, 120 min, and 150 min to obtain a first reaction solution. As a control, under the same experimental conditions, 1.5 g / L dodecyl trimethyl ammonium bromide (DTAB), hexadecyl trimethyl ammonium bromide (CTAB) and an accelerator mixed in a ratio of 1:1 are added.
[0058] After the treatment, the first reaction liquid was taken out, PET was filtered out, washed with ethanol 3 times, washed with deionized water 3 times, dried, weighed, and the degradation rate was calculated. Figure 7 As shown. Figure 7 It can be seen that as the temperature increases, the degradation rate also increases. Without the addition of an accelerator, the degradation rate will not exceed 80% as time increases. After the addition of an accelerator, the degradation rate reaches more than 85% at 30 minutes.
[0059] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0060] The above-mentioned specific implementation methods are used to explain the present invention and are only preferred embodiments of the present invention, rather than limiting the present invention. Any modifications, equivalent substitutions, improvements, etc. made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. An application of a composite catalyst material based on rapid degradation of microplastics in catalytic ozone degradation of organic pollutants in wastewater, characterized in that: The method for preparing the composite catalyst material for rapid degradation of microplastics comprises the following steps: (1) adding an alkaline aqueous solution to microplastics with a particle size of 100 nm to 1000 μm, and then adding an accelerator to perform a hydrolysis reaction to obtain a first reaction solution; The microplastic is polyethylene terephthalate; The accelerator is a quaternary ammonium salt type cationic surfactant, and the accelerator is one or more of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and hexadecyldimethylbenzylammonium chloride; The alkaline aqueous solution is a NaOH aqueous solution, and the NaOH concentration is 10-100 g / L; the temperature of the hydrolysis reaction is 60-140°C, and the time of the hydrolysis reaction is 30-150 min; The main components of the first reaction liquid are sodium terephthalate and ethylene glycol, and also include a small amount of phthalocyanine quinone, ethylene dicarboxylate, benzene trimectric acid, and also include trace amounts of 1,4-benzenedicarboxaldehyde, acetylaminobenzoic acid, acetic acid, and dimethyl ether; (2) adding an acid to the first reaction solution to adjust the pH to acidic, and then adding ferric chloride solid powder to carry out a solvothermal reaction to obtain a second reaction solution; (3) Post-treating the second reaction liquid to obtain a composite catalyst material.
2. The use according to claim 1, characterized in that: In the hydrolysis reaction of step (1), the dosage of the microplastics is 0.5~50 g / L.
3. The use according to claim 1, characterized in that: In step (2), the molar ratio of the first reaction solution to ferric chloride is 1:(0.5-3); the temperature of the solvothermal reaction is 100-300°C, and the time of the solvothermal reaction is 2-48 h.
4. The use according to claim 1, characterized in that: The post-treatment comprises: centrifuging the second reaction liquid to separate the solid from the liquid, washing with DMF and ethanol continuously, and placing the obtained solid in a vacuum drying oven; wherein the vacuum drying temperature is 50-150° C., and the vacuum drying time is 2-48 hours.
